Air pollution associated acute respiratory inflammation and modification by GSTM1 and GSTT1 gene polymorphisms: a panel study of healthy undergraduates - Xiang Zeng; Ge Tian; Jingfang Zhu; Fuyun Yang; Rui Zhang; Huijun Li; Zhen An; Juan Li; Jie Song; Jing Jiang; Dongling Liu; Weidong Wu (BMC, 2023)
Abstract Epidemiological evidence has linked air pollution with adverse respiratory outcomes, but the mechanisms underlying susceptibility to air pollution remain unclear. This study aimed to investigate the role of glutathione S-transferase (GST) polymorphism in the association between air pollution and lung function levels. A total of 75 healthy young volunteers aged 18-20 years old were recruited for six follow-up visits and examinations. Spirometry was conducted to obtain lung function parameters such as forced vital capacity (FVC), and forced expiratory volume in 1 s (FEV1). Nasal fluid concentrations of interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α), and 8-epi-prostaglandin F2α (8-epi-PGF2a) were measured using ELISA kits. Linear mixed-effect models were used to evaluate the association of air pollutants with respiratory outcomes. Additionally, polymorphisms of glutathione S-transferase mu 1 (GSTM1) and glutathione S-transferase theta 1 (GSTT1) were estimated to explore its role in the association between air pollutants and lung function. We found that short-term exposure to atmospheric particulates such as PM2.5 and PM10 can cause an increase in nasal biomarkers of inflammation, oxidative stress, and lung function, while air gaseous pollutant exposure is linked with decreased lung function, except for CO. Stratification analyses showed that an increase in nasal inflammatory cytokines caused by exposure to atmospheric particulates is more obvious in subjects with GSTM1-sufficient (GSTM1 +) than GSTM1-null (GSTM1 − ), while elevated lung function levels due to air particles are more significant in subjects with the genotype of GSTM1 − when compared to GSTM1 +. As for air gaseous pollutants, decreased lung function levels caused by O3, SO2, and NO2 exposure is more manifest in subjects with the genotype of GSTM1 − compared to GSTM1 +. Taken together, short-term exposure to air pollutants is associated with alterations in nasal biomarkers and lung function levels in young healthy adults, and susceptible genotypes play an important mediation role in the association between exposure to air pollutants and inflammation, oxidative stress, and lung function levels.